PERAN MEDIASI STRES KERJA DALAM HUBUNGAN BEBAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA PADA KARYAWAN PT. DELTA DUNIA SANDANG TEKSTIL (DDST) DEMAK - Rajwa, Jilan Nafiatur; Febriana, Artha; Kadarningsih, Ana; Purusa, Nanda Adhi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study analyzes the impact of Workload and Physical Work Environment on Job Satisfaction of employees of PT. Delta Dunia Sandang Tekstil (DDST) in Demak, with Job Stress as an intermediary variable. Using 180 samples and multiple linear regression analysis (Smartpls v4), it was found that Workload, Physical Work Environment, and Job Stress significantly affect Job Satisfaction. Physical Work Environment has the greatest influence on Job Stress (effect size 0.785), indicating the importance of a good work environment to reduce stress. Job Stress is also significant on Job Satisfaction (effect size 0.147), confirming that stress management increases satisfaction. Workload also has a strong influence on Job Satisfaction (effect size 0.293) and Job Stress (effect size 0.145), highlighting the need for a balanced workload. However, the direct effect of Physical Work Environment on Job Satisfaction in this model is not significant.